The Green Six Sigma Handbook A Complete Guide for Lean Six Sigma Practitioners and Managers. - Basu, Ron (Productivity Press, 2022)
This book is a hands-on single-source reference of tools, techniques, and processes integrating both Lean and Six Sigma. This comprehensive handbook provides up-to-date guidance on how to use these tools and processes in different settings, such as start-up companies and stalled projects, as well as establish enterprises where the ongoing drive is to improve processes, profitability, and long-term growth. It contains the "hard" Six Sigma approach as well as the flexible approach of FIT SIGMA, which is adaptable to manufacturing and service industries and also public sector organisations. You will also discover how climate change initiatives can be accelerated to sustainable outcomes by the holistic approach of Green Six Sigma. The book is about what we can do now with leadership, training, and teamwork in every sphere of our businesses. Lean, originally developed by Toyota, is a set of processes and tools aimed at minimising wastes. Six Sigma provides a set of data-driven techniques to minimise defects and improve processes. Integrating these two approaches provides a comprehensive and proven approach that can transform an organisation. To make change happen, we need both digital tools and analog approaches. We know that there has been a continuous push to generate newer approaches to operational excellence, such as Total Quality Management, Six Sigma, Lean Sigma, Lean Six Sigma, and FIT SIGMA. It is vital that we harness all our tools and resources to regenerate the economy after the Covid-19 pandemic and make climate change initiatives successful for the survival of our planet. Six Sigma and its hybrids (e.g., Lean Six Sigma) should also play a significant part. Over the last three decades, operational performance levels of both public sector and private sector organisations improved significantly and Lean Six Sigma has also acted as a powerful change agent. We urgently need an updated version of these tools and approaches. The Green Six Sigma Handbook not only applies appropriate Lean and Six Sigma tools and approaches, fitness for the purpose, but it aims at sustainable changes. This goal of sustainability is a stable bridge between Lean Six Sigma and climate change initiatives. Hence, when the tools and approaches of Lean Six Sigma are focused and adapted primarily to climate change demands, we get Green Six Sigma.